Full catastrophe living - Savich, Zach (Iowa poetry prize., 2009)
"Merging the spirits of Don Quixote, Shakespearean fools, Theodore Roethke, Frank O'Hara, James Merrill, and the Marx Brothers, Zach Savich's first book does more than showcase the innovative fluency of its roving forms and moods: these poetic hybrids are not hothouse blossoms but minotaurs. With ebullient intelligence and high-stakes insistence on the panic, lust, and suffering of the sensual world, Full Catastrophe Living uses the self as an instrument to investigate art, love, and the hardest honesty."--Public metadata view, summary.